St. Louis Paper - The Southern Extremity of the “Clinton” Gas Pools in Ohio - L. S. Panyity (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
The Cleveland (0.) gas pool described by Frank R. Van Horn,' is the northern extremity of the great "Clinton" sand gas development in Ohio. Numerous gas pools have been developed in this formation, which are now more or less connected, link by link, forming an almost continuous gas pool, starting at Cleveland, and running thence southward through Cuyahoga, Medina, Wayne, Ashland, Richland, Knox, Licking,